(untitled) (Materiali di Estetica. Terza serie, 2020)
Imre Kertész (Budapest 1929-2016), Hungarian Jewish, was deported to Auschwitz in 1944, and freed in Buchenwald in 1945. For him the concentration camp experience and the reflection on the Shoah were and remain fundamental also in the elaboration of a commitment in favor of Europe. Kertész was indeed very fond of a certain idea of Europe for which he engaged himself with writing his memoirs and his novels and with numerous public lectures. The idea of Europe was dear to him not only in the years of the lager, but also in the era of the so-called "real socialism" and until the end of his days, in which the survival of Europe was already at risk, not only in Hungary. To all these anti-democratic motions he responded with the joy of writing, which gives voice to the values and hopes that despite everything to him (and hopefully for us) remain alive.